If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 4 = 7(y + -1) Reorder the terms: 4 + 8y = 7(y + -1) Reorder the terms: 4 + 8y = 7(-1 + y) 4 + 8y = (-1 * 7 + y * 7) 4 + 8y = (-7 + 7y) Solving 4 + 8y = -7 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 4 + 8y + -7y = -7 + 7y + -7y Combine like terms: 8y + -7y = 1y 4 + 1y = -7 + 7y + -7y Combine like terms: 7y + -7y = 0 4 + 1y = -7 + 0 4 + 1y = -7 Add '-4' to each side of the equation. 4 + -4 + 1y = -7 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = -7 + -4 1y = -7 + -4 Combine like terms: -7 + -4 = -11 1y = -11 Divide each side by '1'. y = -11 Simplifying y = -11
| y=(x^2)(sinx)(tanx) | | 5-(4-9)= | | -8x+4+9x=-13+3 | | 6z^2-37z-553=0 | | 3x+5=175 | | y+4.4=-7.7-8.2 | | 10-3x=-5k | | 4x^2-44=1835 | | -2-4=-8+x | | x-.4=4.4 | | -7+17t= | | -23+11=m-8 | | 6x+10=12x-8 | | 5(x-2)-3(x-2)=2x+4 | | 5t-12t= | | x+1overx=6 | | 14x(x-y)+(x-y)=0 | | 6x-2(-6x+7)=130 | | 2(x^2-476)=0 | | 42=-7x | | 510=-10(-8x+5) | | ln(x)=ln(8)-2ln(x) | | 10-49=39 | | 4p-6=18 | | 4x+2(3x+4)=128 | | 5(x+2)-3(x-2)=2x+4 | | -38=-4x+5(4x+18) | | P(7)+P(8)+P(9)+P(10)+P(11)+P(12)+P(13)+P(14)= | | 2h+12=8h-36 | | 5(-6x+13)=275 | | 34-35= | | -9(-6x+8)=468 |